THE EFFECT OF PORPE METHOD(PREDICT, ORGANIZE, REHEARSE, PRACTICE, EVALUATE)ON STUDENTS’ READING COMPREHENSION OF REPORT TEXT AT THE ELEVENTH TKJ STUDENTS OF SMK NEGERI 1 LUMUT IN 2021/2022 ACADEMIC YEAR - K Sabda Liana Aritonang (JURNAL LINER (Language Intelligence and Educational Research), 2022)
ABSTRACT: The purposes of this research are to know: 1) the application of PORPE method on teaching reading comprehension of report text, 2) the students’ reading comprehension before and after using PORPE method, 3) Whether there is any significant effect of PORPE method on teaching reading comprehension of report text at the XI TKJ students of SMK Negeri 1 Lumut. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the XI TKJ students’ of SMK Negeri 1 Lumut which consist of 106 students. Sample were XI TKJ1 which consist of 36 students which taken by purposive sampling. In collecting data the researcher uses observation sheet and oral test as an instrument. The result of this research: 1) the application of PORPE method was 3.8, it was categorized “Very Good”. 2) the mean score of the students’ speaking ability was 56 and it was categorized “fail”. Meanwhile, after using point counter point strategy was 82, it is categorized “Very Good”. The result of data analysis shows that ttest was higher than ttable(ttest 30.22>ttable2.03). So, the hypothesis was accepted. It means that, there is any significant effect of PORPE method on students’ reading comprehension of report text at the eleventh TKJ students of SMK Negeri 1 Lumut. Keywords: PORPE Method, Reading Comprehension, Report Text Abstrak: Tujuan penelitian ini adalah unuk mengetahui : 1) penggunaan metode PORPE dalam mengajar pemahaman membaca, 2) pemahaman membaca siswa sebelum dan sesudah pengaplikasian metode PORPE, 3) apakah ada pengaruh yang signifikan dari metode PORPE terhadap pemahaman membaca di kelas XI TKJ1 SMK Negeri 1 Lumut. Penelitian ini menggunakan metode eksperimental dengan rancangan penelitian pre eksperimental: one group pre-test post-test design. Jumlah populasi 106 siswa dan 36 jumlah sampel dengan menggunakan teknik purposive sampling. Dalam pengumpulan data peneliti menggunakan lembar observasi dan tes lisan. Hasil dari penelitian: 1) penggunaan metode PORPE mendapat nilai 3.8 yang dikategorikan “sangat baik”, 2) nilai pemahaman siswa dalam membaca teks report 56 dan dikategorikan “gagal”. Sedangkan, setelah penggunaan metode PORPE nilai pemahaman siswa dalam membaca teks report adalah 82 dan dikategorikan “sangat baik”. Hasil dari penelitian menunjukkan bahwa ttest lebih tinggi dari ttble (ttest 30.22. >ttable2.03). hal ini menunjukkan bahwa hipotesis diterima. Dan menunjukkkan bahwa ada pengaruh yang signifikan dari penggunaan metode PORPE terhadap pemahaman membaca teks report siswa di kelas XI TKJ1 SMK Negeri 1 Lumut Tahun Ajaran 2021/2022. Kata kunci: Metode PORPE, Pemahaman Membaca, Teks Report